FRI0366 Primary respiratory disease in patients with systemic lupus erythematosus: data from the spanish rheumatology society lupus registry (RELESSER) cohort. (12th June 2018) - Narvaez, J.; Borrell, H.; Sánchez-Alonso, F.; Rúa-Figueroa, I.; Lopez-Longo, F.J.; Galindo, M.; Calvo-Alen, J.; Fernández-Nebro, A.; Olivé, A.; Andreu, J.L.; Blanco, R.; Andres, M.; et al.
Abstract : Objectives: To investigate the primary respiratory manifestations (PRM) in SLE. Methods: All patients in the RELESSER cohort were retrospectively investigated for the presence of PRM Results: At least one PRM was present in 11.3% (365/3215) of cases. The most common was pleurisy, occurring in 21.1% of patients, followed by ALP in 3.6%, PE in 2.9%, PPH 4%, DILD in 2%, DAH in 0.8%, and SLS in 0.8%. The variables associated with the presence of PPM are shown in the following table 1: Conclusions: PPM independently contributed to a decreased survival in SLE Disclosure of Interest: None declared